Kajian Kesalahan Berbahasa dalam Media Sosial : Studi Kasus pada Akun Twitter Tokoh Publik - Muhammad Trisnadi; Nabila Miftahani Akmal; Intan Sari Ramdhani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article examines the increasingly widespread phenomenon of errors in the use of Indonesian on social media, particularly on Twitter. The research was conducted using a literature review method and a descriptive-qualitative approach to identify the types of language errors and analyze their causal factors. The analysis shows that errors occur in various forms, including phonology, morphology, syntax, and diction that does not conform to the Enhanced Spelling (EYD) rules. Tweets by public figures such as @sudjiwotedjo and @andihiyat serve as important examples to illustrate spelling errors and illocutionary speech acts that have pragmatic and social implications. The use of informal language, abbreviations, and emojis also reinforces the tendency for language errors in the digital realm. This article concludes that linguistic awareness needs to be increased to maintain the use of Indonesian in the digital age.